Theorising pornogrammar in the Akan folktale tradition: The trickster’s rhetorical indirection and sexual indiscretion. - Amissah-Arthur, J. B. (Legon Journal of the Humanities, 2019)
In the oral and written folktale tradition of the Akan people of Ghana, Kweku Ananse is the archetypal trickster. Simultaneously, he is divinity and mortal, anthropomorphic and zoomorphic, mind and matter, culture hero and comical villain. Though the phenomenon of Ananse has been widely studied, the question of Ananse’s sexually-oriented verbal traps has received very little or no attention. The present essay attempts to contribute towards filling this gap by raising fundamental questions about Ananse’s language. What linguistic stratagem informs the apparent ease with which he appropriates other people’s wives? We find that as the quintessential linguist, Ananse’s mastery of rhetorical indirection is fundamental to his success as a libertine. The essay examines the forms of rhetorical indirection and linguistic stratagem by which Ananse negotiates sex, whether he is taking advantage of a friend’s wife, seducing the king’s daughter or appropriating Nana Nyakopon the Supreme God’s spouse.